Adverse and hormetic effects in rats exposed for 12 months to low dose mixture of 13 chemicals: RLRS part III. (August 2019) - Docea, Anca Oana; Goumenou, Marina; Calina, Daniela; Arsene, Andreea Letitia; Dragoi, Cristina Manuela; Gofita, Eliza; Pisoschi, Catalina Gabriela; Zlatian, Ovidiu; Stivaktakis, Polychronis D.; Nikolouzakis, Taxiarchis Konstantinos; Kalogeraki, Alexandra; Izotov, Boris N.; et al.
Graphical abstract: Highlights: Exposure to very low dose of chemicals mixture can lead in various adverse effects. Monotonic increase of appetite in both sexes and of body weight gain in females. Non-monotonic effects on anabolism, AST, ALT and PChE in males. Monocytes significantly increased in both sexes only in low dose group. TNF-α and IFN-γ increased in male rats from medium dose groups. Abstract: The aim of the current study was to evaluate the effects of a mixture of thirteen common chemicals on rats, after a one-year exposure to doses around the acceptable daily intake (ADIs), using blood and urinary tests. The influence of low doses of the mixture on weight gain, water consumption, feed consumption and feed efficiency, biochemistry parameters, haematological parameters, blood lymphocytes subsets, serum inflammation profile and urine parameters was evaluated. Our mixture caused a moderate monotonic increase of the males' appetite and a non-monotonic increase of anabolism and a monotonic increase of appetite for the females. Regarding biochemical parameters, the exposure to the test mixture caused non-monotonic increases of AST and ALT, a decrease of PChE in males and plausibly a monotonic biliary obstruction in both sexes. Monocytes significantly increased in low dose groups of both sexes. A significant decrease of all the lymphocytes subclasses and an increased expression of TNF-α protein associated with an increased expression of IFN-γ protein observed in various groups. It became apparent that after twelve months of exposure very low doses of the tested mixture had both non-monotonic and monotonic harmful effects on different levels on rats.